[View of scaffolding used during construction] - P. K. Phillips::::::photographer::: (1978)
View of the scaffolding used during the construction of the interior of Kennedy Library. The main staircase and atrium are visible. This image was captured after a rainstorm, resulting in the materials and structure in the image being wet.